Pengaruh Rehabilitasi Saluran Induk Kalibawang Terhadap Pengembangan Ekonomi Wilayah Kecamatan Kalibawang Kabupaten Kulon Progo - Andika, Muhamat; Sunaryo, Broto (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
One of the irrigation infrastructure developments realized by the government is Kalibawang Irrigation Canal in Kulon Progo regency. The rehabilitation of Kalibawang Primary Canal in 2010 and 2011 is expected to be beneficial for the society’s corps. This study aims at describe the effect of the rehabilitation of Kalibawang Primary Canal towards the economy development of Kalibawang Subdistrict by considering the extensification of agriculture, the intensification of agriculture, the rice production, the agricultural activity in upstream and downstream, and the pattern and structure of the space. This study is quantitative research which is supported by the descriptive analysis as well as superimposes spatial analysis technique. The findings of this study conclude that the rehabilitation of Kalibawang Primary Canal gives positive effect upon the economy development in Kalibawang Subdistrict of Kulon Progo Regency.